Giant Cell Tumour of the Distal Humerus: A Case Report - Atmananda S Hegde; Ravindra M Shenoy; Mahabala P Rai (Journal of Orthopaedic Surgery, 2014)
Giant cell tumour of the distal humerus is rare. We report one such case in a 30-year-old man who underwent wide resection of the tumour followed by total elbow arthroplasty using a cemented ‘sloppy-hinged’ total elbow prosthesis. At the 18-month follow-up, the patient had pain-free range of motion of 15° to 120° and no evidence of recurrence.